Proteome analysis of an attenuated Francisella tularensis dsbA mutant: identification of potential DsbA substrate proteins - Straskova, Adela; Pavkova, Ivona; Link, Marek; Forslund, Anna-Lena; Kuoppa, Kerstin; Noppa, Laila; Kroca, Michal; Fucikova, Alena; Klimentova, Jana; Krocova, Zuzana; Forsberg, Ake; Stulik, Jiri (Journal of proteome research, 2009)
Francisella tularensis (F. tularensis) is highly infectious for humans via aerosol route and untreated infections with the highly virulent subsp. tularensis can be fatal. Our knowledge regarding key virulence determinants has increased recently but is still somewhat limited. Surface proteins are potential virulence factors and therapeutic targets, and in this study, we decided to target three genes encoding putative membrane lipoproteins in F. tularensis LVS. One of the genes encoded a protein with high homology to the protein family of disulfide oxidoreductases DsbA. The two other genes encoded proteins with homology to the VacJ, a virulence determinant of Shigella flexneri. The gene encoding the DsbA homologue was verified to be required for survival and replication in macrophages and importantly also for in vivo virulence in the mouse infection model for tularemia. Using a combination of classical and shotgun proteome analyses, we were able to identify several proteins that accumulated in fractions enriched for membrane-associated proteins in the dsbA mutant. These proteins are substrate candidates for the DsbA disulfide oxidoreductase as well as being responsible for the virulence attenuation of the dsbA mutant.
Keywords: proteom; Membrane Proteins; Chromatography, Liquid; Humans; Proteomics; Molecular Sequence Data; molekulární sekvence - údaje; mutace; makrofágy; Tularemia; Francisella tularensis; myši inbrední BALB C; lidé; zvířata; myši; Protein Disulfide-Isomerases; proteomika; proteindisulfidisomerasy; bakteriální proteiny; peptidy; faktory virulence; Mice; Peptides; buněčné linie; chromatografie kapalinová; Cell Line; isoelektrická fokusace; Isoelectric Focusing; tularemie; Bacterial Proteins; membránové proteiny; Proteome; Animals; Macrophages; míra přežití; Mutation; hmotnostní spektrometrie; Virulence Factors; Mice, Inbred BALB C; Mass Spectrometry; Survival Rate